Estimating the cost of vaccine development against epidemic infectious diseases: a cost minimisation study - Dimitrios Gouglas, MSc; Tung Thanh Le, MSc; Klara Henderson, PhD; Aristidis Kaloudis, ProfPhD; Trygve Danielsen, MSc; Nicholas Caspersen Hammersland, MSc; James M Robinson, MS; Penny M Heaton, MD; John-Arne Røttingen, ProfMD (Elsevier, 2018)
Summary: Background: The Coalition for Epidemic Preparedness Innovations was established in 2016, to develop vaccines that can contribute to preparedness for outbreaks of epidemic infectious diseases. Evidence on vaccine development costs for such diseases is scarce. Our goal was to estimate the minimum cost for achieving vaccine research and development preparedness targets in a portfolio of 11 epidemic infectious diseases, accounting for vaccine pipeline constraints and uncertainty in research and development preparedness outcomes. Methods: We assembled a pipeline of 224 vaccine candidates from preclinical through to phase 2 for 11 priority epidemic infectious diseases. We used a linear regression model to identify drivers of development costs from preclinical through to end of phase 2a. Drawing from published estimates of vaccine research and development probabilities of success, we simulated costs for advancing these 224 vaccine candidates through to the end of phase 2a. We combined these findings to determine minimum costs for progressing at least one vaccine through to the end of phase 2a per epidemic infectious disease by means of a stochastic optimisation model. Findings: The cost of developing a single epidemic infectious disease vaccine from preclinical trials through to end of phase 2a is US$31-68 million (US$14-159 million range), assuming no risk of failure. We found that previous licensure experience and indirect costs are upward drivers of research and development costs. Accounting for probability of success, the average cost of successfully advancing at least one epidemic infectious disease vaccine through to the end of phase 2a can vary from US$84-112 million ($23 million-$295 million range) starting from phase 2 to $319-469 million ($137 million-$1·1 billion range) starting from preclinical. This cost includes the cumulative cost of failed vaccine candidates through the research and development process. Assuming these candidates and funding were made available, progressing at least one vaccine through to the end of phase 2a for each of the 11 epidemic infectious diseases would cost a minimum of $2·8-3·7 billion ($1·2 billion-$8·4 billion range). Interpretation: Our analysis provides new evidence on vaccine research and development pipelines and associated costs for 11 epidemic infectious diseases, highlighting both funding needs and research and development gaps for achieving vaccine research and development preparedness targets. Funding: This work was partly supported by the Research Council of Norway through the Global Health and Vaccination Programme GLOBVAC.